Structuring and restructuring COVID-19 Intensive Care Units: a systematic review - Luis Fernando Reis Macedo; Kenya Waléria de Siqueira Coelho Lisboa; Thais Rodrigues de Albuquerque; Alexandre Pazetto Balsanelli; Sarah De Lima Pinto; Izabel Cristina Santiago Lemos de Beltrão; Gyllyandeson de Araujo Delmondes (Revista de Epidemiologia e Controle de Infecção)
Background and Objectives: the COVID-19 pandemic imposed restructuring and reorganization in healthcare services, particularly in Intensive Care Units (ICUs), due to the increased demand for hospital care for the thousands of severe cases of the disease. Thus, understanding this ICU reorganization process is useful for healthcare system planning and, consequently, for preventing system collapse in the face of impending pandemics. The objective was to identify elements related to the restructuring and organization of human resources, materials, and organization/structure processes in ICUs during the COVID-19 pandemic. Methods: this is a qualitative systematic review. Searches were conducted in the MEDLINE, PubMed, Scopus, Web of Science, and Embase databases. The results were exported to the Rayyan software for subsequent screening and blind selection by two independent researchers as well as for assessing the risk of bias and individual methodological quality of selected studies. Results: a total of 171 articles were found across the five databases, with five articles selected to be included in this review. The identified elements concerning the restructuring and organization of ICUs were the use and availability of personal protective equipment, oxygen, and oxygen therapy equipment, medications, psychological support for healthcare professionals, patient safety measures, and space maintenance. Conclusion: this review allowed for the compilation and synthesis of necessary elements for the restructuring and organization of ICUs during the pandemic, considering the need for managers to respond swiftly to the high demand brought on by COVID-19.